Transcriptome analysis of Escherichia coli K1 after therapy with hesperidin conjugated with silver nanoparticles - Masri, Abdulkader (2021)
Backgrounds: Escherichia coli K1 causes neonatal meningitis. Transcriptome studies are indispensable to comprehend the pathology and biology of these bacteria. Recently, we showed that nanoparticles loaded with Hesperidin are potential novel antibacterial agents against E. coli K1. Here, bacteria were treated with and without Hesperidin conjugated with silver nanoparticles, and silver alone, and 50% minimum inhibitory concentration was determined. Differential gene expression analysis using RNA-seq, was performed using Degust software and a set of genes involved in cell stress response and metabolism were selected for the study. Results: 50% minimum inhibitory concentration with silver-conjugated Hesperidin was achieved with 0.5 μg/ml of Hesperidin conjugated with silver nanoparticles at 1 h. Differential genetic analysis revealed the expression of 122 genes (≥ 2-log FC, P< 0.01) in both E. coli K1 treated with Hesperidin conjugated silver nanoparticles and E. coli K1 treated with silver alone, compared to untreated E. coli K1. Of note, the expression levels of cation efflux genes (cusA and copA) and translocation of ions, across the membrane genes (rsxB) were found to increase 2.6, 3.1, and 3.3- log FC, respectively. Significant regulation was observed for metabolic genes and several genes involved in the coordination of flagella. Conclusions: The antibacterial mechanism of nanoparticles maybe due to disruption of the cell membrane, oxidative stress, and metabolism in E. coli K1. Further studies will lead to a better understanding of the genetic mechanisms underlying treatment with nanoparticles and identification of much needed novel antimicrobial drug candidates.